Pretreatment Neutrophil-to-Lymphocyte Ratio: A Predictor of Advanced Prostate Cancer and Biochemical Recurrence in Patients Receiving Radical Prostatectomy. Issue 41 (October 2015) - Zhang, Gui-Ming; Zhu, Yao; Ma, Xiao-Cheng; Qin, Xiao-Jian; Wan, Fang-Ning; Dai, Bo; Sun, Li-Jiang; Ye, Ding-Wei
Abstract : Abstract: The pretreatment neutrophil-to-lymphocyte ratio (NLR) is reportedly associated with the clinical outcomes of many cancers. However, it has not been widely investigated whether the pretreatment NLR is associated with the pathological characteristics of prostate cancer (PCa) and biochemical recurrence in PCa patients receiving radical prostatectomy (RP). In this cohort study, a total of 1688 PCa patients who had undergone RP were analyzed retrospectively, and a subset of 237 of these patients were evaluated to determine the relationship between pretreatment NLR and biochemical recurrence. Patients were divided into a high-NLR group (NLR ≥2.36) and a low-NLR group (NLR < 2.36) according to the pretreatment NLR. The association between the pretreatment NLR and pathological stage and lymph node involvement was evaluated using logistic regression analysis. Time of biochemical recurrence was determined using the Kaplan–Meier method. Cox's proportional hazard regression model was used to compare the time of biochemical recurrence between the groups. As compared with patients in the low-NLR group, those in the high-NLR group had an increased risk of pT3–4 disease (odds ratio (OR), 1.883; 95% confidence interval (CI), 1.419–2.500; P < 0 .001), and a 1.7-fold increased risk of lymph node involvement (OR, 1.685; 95% CI, 1.101–2.579; P = 0 .016). For the subset of 237 patients, those with a high NLR showed a significantly shorter median biochemical recurrence-free survival time (51.9 months) than those with a low NLR (76.5 months; log-rank test, P = 0 .019). However, multivariate analysis indicated that the NLR was not an independent predictor of biochemical recurrence (hazard ratio, 1.388; 95% CI, 0.909–2.118; P = 0 .129). Our findings suggest that the pretreatment NLR may be associated with pathological stage and lymph node involvement in PCa patients receiving RP, and that PCa patients with a high NLR may have a higher rate of biochemical recurrence following RP than those with a low NLR.